Characteristics of First-Year Residents in Top-Ranked United States Ophthalmology Residency Programs - Lin, John C.; Lokhande, Anagha; Chen, Allison J.; Scott, Ingrid U.; Greenberg, Paul B. (Journal of Academic Ophthalmology, 2022)
Objective The aim of the study is to investigate the characteristics of first-year residents associated with attending a top-ranked United States (U.S.) ophthalmology residency program over the past decade.Methods First-year ophthalmology residents in 2009, 2013, 2016, and 2019 were identified from institutional websites, Doximity, LinkedIn and the Wayback Machine. Publications were obtained from Scopus and Google Scholar; research productivity was measured using the h-index, and medical school region based on U.S. Census Bureau designations. Medical school and ophthalmology training program rankings were based on U.S. News & World Report (U.S. News) rankings and National Institutes of Health (NIH) funding. One-way ANOVA, Wilcoxon rank sum, χ2, and t-tests were used to analyze trends, and odds ratios (ORs) were calculated using logistic regression.Results Data were obtained on 81% (1,496/1,850) of the residents; 43% were female; 5% were international medical graduates (IMGs); and 10% had other graduate degrees. Over the decade, the mean h-index increased (0.87–1.26; p <0.05) and the proportion of residents who attended a top 20 medical school decreased (28–18%; p <0.05). In a multivariate logistic regression model, characteristics associated with being a first-year resident in a top 20 program ranked by U.S. News were female gender [OR: 1.32, 95% CI: 1.02–1.72], having a Master's degree [OR: 2.28, 95% CI: 1.29–4.01] or PhD [OR: 2.23, 95% CI: 1.32–3.79], attending a top 20 [OR: 5.26, 95% CI: 3.66–7.55] or a top 40 medical school by NIH funding [OR: 2.45, 95% CI: 1.70–3.54], attending a medical school with a mean USMLE Step 2 score above 243 [OR: 1.64, 95% CI: 1.01–2.67] or located in the Northeast [OR: 2.00, 95% CI: 1.38–2.89] and having an h-index of one or more [OR: 1.92, 95% CI: 1.47–2.51]. Except for gender, these characteristics were also significantly associated with matching to a top 20 ophthalmology program by NIH funding.Conclusion Female gender, graduate degrees, research productivity, and attending a medical school with high research productivity, high mean USMLE Step 2 score or in the Northeast were key characteristics of first-year residents in top-ranked U.S. ophthalmology residency programs.
Keywords: ophthalmology; residency; residency match; research productivity